Effect of ketoprofen and tolfenamic acid on intravenous pharmacokinetics of ceftriaxone in sheep - Cetin, Gul; Durna Corum, Duygu; Corum, Orhan; Atik, Orkun; Coskun, Devran; Uney, Kamil (Wiley, 2021)
AbstractIn this study, the pharmacokinetics of ceftriaxone (40 mg/kg) was determined following a single intravenous (IV) administration of ceftriaxone alone and co‐administration with ketoprofen (3 mg/kg) or tolfenamic acid (2 mg/kg) in sheep. Eight healthy Akkaraman sheep (2.4 ± 0.3 years and 44 ± 4 kg of body weight) were used. The study was carried out according to the longitudinal design in three periods with a 15‐day washout period between administrations. In the first period, sheep received ceftriaxone alone via an IV injection. In the second and third periods, the same sheep received ceftriaxone in combination with ketoprofen and tolfenamic acid, respectively. Plasma concentrations of ceftriaxone were assayed by high‐performance liquid chromatography and analyzed using non‐compartmental analysis. Following the administration of ceftriaxone alone, the elimination half‐life (t1/2ʎz), area under the plasma concentration–time curve from zero (0) hours to infinity (∞) (AUC0‐∞), total clearance (ClT), and volume of distribution at steady state were 1.42 h, 182.41 h*µg/ml, 0.22 L/h/kg, and 0.17 L/kg, respectively. While ketoprofen and tolfenamic acid significantly increased the t1/2ʎz and AUC0‐∞ of ceftriaxone, they significantly reduced the ClT. Ceftriaxone (40 mg/kg, IV) in concurrent use with ketoprofen and tolfenamic acid can be administrated at the 12 h dosing intervals to maintain T> minimum inhibitory concentration (MIC) values above 60% in the treatment of infections caused by susceptible pathogens with the MIC value of ≤0.75 and ≤1 μg/mL, respectively, in sheep with an inflammatory condition.
Keywords: sheep; ketoprofen; Sheep; Ceftriaxone; tolfenamic acid; ceftriaxone; Ketoprofen; Area Under Curve; Injections, Intravenous; Animals; ortho-Aminobenzoates; pharmacokinetics; Half-Life; 2. Zero hunger